Kajian Konseptual Pengambilan Keputusan Pada Sistem Manajemen Pendidikan Islam: Conceptual Study of Decision Making in Islamic Education Management System - Humairoul Muhlisoh (Qudwah: Journal of Islamic Education, 2026)
Decision-making in Islamic education management holds a strategic position because it is the primary indicator of the success of educational institution management. This process serves as a mechanism for resolving various organizational issues in order to achieve predetermined goals. In the context of Islamic educational institutions, a crucial initial step is analyzing the problems by classifying them into simple, complex, structured, and unstructured categories to determine the most appropriate type of decision. The principle of deliberation and consensus is a typical approach used in certain situations, involving various parties, such as educational staff, students, parents, and the community. Furthermore, the leader's leadership style and personal character also influence the quality of decisions made. The principal is expected to be able to formulate decisions that align with the institution's vision and mission through the development of systematic, sustainable, and well-planned programs for both the short and long term.